The role of design against the pandemic: field actions and contributions in time of crisis (Revista de Ensino em Artes, Moda e Design, 2023)
This article aims to analyze the role of the Design as a tool in the battle agains the Covid-19 pandemic. It is a study with a qualitative approach of the bibliographic and descriptive type, using the interface of knowledge of design in its different areas of activity evidencing the important contributions of the field and of its practitioners in the pandemic context. Cardoso (2008, 2012), Forty (2007), Margolin (2014), Ingold (2019) and Papanek (1995) were the theoretical bases for this study, in which were analyzed some cases and examples of problems arising from the health crisis. The study was guided by the following question: What is the potential of the Design in the fight against the health crisis and how can this area contribute to overcoming an abstruse panorama such as the one that brought the pandemic? It was concluded that the designer’s ability to create bridges and establish relationships in an increasingly fragmented world of knowledge allows him to create systemic and creative solutions to the increasingly challenging problems of humanity.
Keywords: Design; Design and pandemic; Design and crisis